Edukasi Tentang Keteraturan Kunjungan Antenatal Care - Suganda, Yohana; Gusmadewi, Gusmadewi; Radhia, Mekar Zenni; Silvia, Elwitri; Zaini, Hanifa; Sari, Endang (Universitas Sumatera Barat, 2023)
Antenatal care aims to see how the fetus grows and develops and aims to improve the welfare of the mother and fetus. WHO's efforts to reduce the number of high-risk pregnancies include routine examinations for all pregnant women, as well as follow-up examinations for mothers with moderate comorbidities and complications, obstetric and neonatal examinations for women with severe comorbidities and complications. Yeoh et al, (2016) stated that as many as 26% of women with high-risk pregnancies never had an Antenatal Care examination or visit. while 80% of pregnant women experience no complications, and carry out regular Antenatal Care visits according to the recommended re-visit schedule. Pregnant women who do not regularly carry out prenatal checks will have a risk of experiencing pregnancy complications such as chorioamnionitis, placental abruption and a 10x greater risk of giving birth to a baby with a low birth weight, a 12x greater risk of fetal death and a 10x greater risk of maternal death